Study on the polymorphic loci of explosive strength-related genes in elite wrestlers - Qi, S.; Yu, J.; Meng, F.; Wei, Z.; Liang, Z. (Genes, 2024)
This investigation aimed to explore the relationship between Chinese elite wrestlers and the polymorphic loci of explosive strength genes, and to further explore the feasibility of its application to athlete selection. The snapshot technique was used to resolve the polymorphic loci of explosive power genes in the wrestler group (59 elite wrestlers) and the control group (180 ordinary college students), and to analyze the genotype frequencies and allele frequencies of each group. A chi-square test was performed on the genotype and allele distribution data of each group to analyze the loci of explosive power genes that were associated with elite wrestlers. The loci that had an association with elite wrestlers were combined with the genotyping data, and the dominance ratios of the genotypes were calculated using the chi-square test to determine the dominant genotypes associated with elite wrestlers. The VDR gene rs2228570 locus exhibited statistically significant differences in genotype and allele distributions between elite wrestlers and the general population (p < 0.01). At the rs2228570 locus of the VDR gene, the difference between the CC genotype and other genotypes was statistically significant (p < 0.05). The rs2228570 locus of the VDR gene was identified as the locus associated with Chinese elite wrestlers. The polymorphism of the VDR gene can be used as a biomarker for Chinese wrestlers, and the CC genotype can be used as a molecular marker for the selection of Chinese elite athletes in this sport. However, expanding the sample size of elite athletes is necessary to further validate the scientific validity and feasibility of these findings.